(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
The Triacontanol is a plant growth stimulator used in field crops. The easy availability of Triacontanol is frequently encountered in forensic cases. The aim of present paper is to describe symptoms, postmortem changes occur in a reported case of Triacontanol plant growth stimulator and detection and identification of plant growth stimulator in visceral material by T.L.C. method.